Disparitas Pemanfaatan Material Bambu: Studi Komparatif Kinerja Fungsi dan Estetika dalam Elemen Bangunan - Afra Hanifa Abni; Atqiya Sajiida Khaufilah Mahbiatulisfar; Kaylla Widiya Putri (GLOBAL SCIENTS PUBLISHER, 2026)
Bamboo is a material frequently used in architectural works. Over time, bamboo's function has shifted as a building element. This expansion has led to bamboo being viewed not only as a structural element but also as the face of a building. The use of bamboo in various building typologies naturally demonstrates differences in processing and emphasis on its character and expression, depending on the typological context. This creates disparities in the effectiveness of bamboo application in each building. This study uses a comparative quantitative approach through user perception surveys and architect interviews with several building typologies. Quantitative findings reveal that users tend to appreciate bamboo in buildings that emphasize new spatial experiences and environmental relationships, particularly in the Tourism and Recreation typology. This requires a strong visual identity and integration with its ecological context. Through data analysis comparing user responses and architects as designers, it is revealed that there is a tendency for similar perceptions between the two, leading to the conclusion that it is in buildings with the Tourism and Recreation typology that the performance of bamboo material is optimized, both in terms of aesthetics and contextual relevance.